2019
DOI: 10.1177/2151459318816982
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Inflammation Influence 1-Year Mortality of Surgically Treated Elderly Intertrochanteric Fractures: A Prospective International Multicenter Case Series

Abstract: Introduction:Hip fracture is a common and devastating event in older adults causing increased dependence, comorbidity, and mortality. Since new surgical techniques have not significantly improved the mortality rate, a better understanding of patient risk factors could improve the treatment algorithm and outcomes. This prospective study aimed to document the 1-year survival rate of patients with intertrochanteric fracture treated surgically in Latin America and to investigate risk factors associated with 1-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…In prior publications, laboratory evaluation results, including admission hemoglobin concentration, blood level of albumin, and Neutrophil to lymphocyte ratio (NLR), were found to be significantly related to 30-day or 1-year mortality in patients with a hip fracture [ 3 , 16 , 17 , 18 , 26 , 29 ]. Our results showed that an admission hemoglobin concentration of <10 g/dL was a significant predictor of mortality, a finding in concordance with those studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In prior publications, laboratory evaluation results, including admission hemoglobin concentration, blood level of albumin, and Neutrophil to lymphocyte ratio (NLR), were found to be significantly related to 30-day or 1-year mortality in patients with a hip fracture [ 3 , 16 , 17 , 18 , 26 , 29 ]. Our results showed that an admission hemoglobin concentration of <10 g/dL was a significant predictor of mortality, a finding in concordance with those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin level is one of the factors which has been found to be associated with mortality [ 17 , 29 ]. Unfortunately, the admission serum albumin level in patients was not routinely investigated at our institution during the time of this study: only 151 patients (19%) were examined for serum albumin level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations